Faktor-Faktor yang Mempengaruhi Perilaku Pembelian Konsumen di Toko Online - Rafika Anggraini; Tri Kurniawati (Universitas Negeri Padang, 2022)
Abstract: This study aims to determine: (1) impact of price on consumer purchasing behavior in online shop (2) impact of website quality on consumer purchasing behavior in online shop (3) impact of store reputation on consumer purchasing behavior in online shops. This is quantitative research with a sample of 100 students of the Faculty of Economics, Universitas Negeri Padang. Data is collected by using questionnaire. The methods for data analysis used are descriptive analysis and multiple regression. The results show that Price, Website Quality, and Store Reputation have significant effect on Consumer Purchase Behavior in online shop (Study on FE UNP Students).